Physicochemical Characterization Of Argentinian Honeys From The Phytogeographic Provinces Pampeana, Espinal And Monte Based On Their Sugar Profiles And Quality Parameters - Inés Aubone; Marisa Amadei Enghelmayer; Akram Ali Haji (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The honeys from the Phytogeographic Provinces (PP) of the south of Buenos Aires province (Argentina) were characterised by the sugar composition and physicochemical parameters used for honey quality control. A large set (n=329) of traceable raw honey samples obtained from beekeepers were analysed and met the specifications of the national and/or international standards for the evaluated parameters, which denoted their blossom origin and confirmed their authenticity, good maturity and freshness. The influence of flora and the pedoclimatic conditions of each phytogeographical region, as well as their beekeeping practices, on the physical and chemical properties of honey allowed its characterization. Thus, the honeys from the southeast of Buenos Aires province were characterized by higher contents of moisture, fructose, maltose, erlose, hydroxymethylfurfural (HMF) and ash, pH and electrical conductivity (EC) and slightly lighter colours; while southwest honeys showed higher free acidities, sucrose content and ºBrix values. Honeys from the PP Espinal exhibited characteristic lower contents of fructose, HMF and ash and EC values, and larger amounts of sucrose. Honeys from the PP Monte presented typical lower moisture contents and slightly darker colours. Honeys from the PP Pampeana were typified by higher amounts of fructose.